Safety and efficacy of l‐lysine monohydrochloride and l‐lysine sulfate produced using Corynebacterium glutamicum CCTCC M 2015595 for all animal species. (21st March 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on l ‐lysine monohydrochloride and l ‐lysine sulfate produced using Corynebacterium glutamicum CCTCC M 2015595 when used as nutritional additive in feed and water for drinking for all animal species. The active substance is l ‐lysine and it is produced in two different forms (monohydrochloride or sulfate). Owing to the uncertainties regarding the possible genetic modification of the strain used to obtain the production strain C. glutamicum CCTCC M 2015595 and on the possible presence of viable cells and DNA of the production strain in the final product, the FEEDAP Panel cannot conclude on the safety of the additives l ‐lysine HCl and l ‐lysine sulfate produced with C. glutamicum CCTCC M 2015595 for the target species, the consumers, the users and the environment. For both products, the FEEDAP Panel has concerns regarding the safety for the target species when the additives are administered via water for drinking. In the absence of data, the FEEDAP Panel cannot conclude on the safety of the additive for the user. The products under assessment are considered efficacious sources of the amino acid l ‐lysine for all animal species. For these products to be as efficacious in ruminants as in non‐ruminant species, they require protection against degradation in the rumen.